2021
DOI: 10.1038/s42004-020-00441-7
|View full text |Cite
|
Sign up to set email alerts
|

Local structure and distortions of mixed methane-carbon dioxide hydrates

Abstract: A vast source of methane is found in gas hydrate deposits, which form naturally dispersed throughout ocean sediments and arctic permafrost. Methane may be obtained from hydrates by exchange with hydrocarbon byproduct carbon dioxide. It is imperative for the development of safe methane extraction and carbon dioxide sequestration to understand how methane and carbon dioxide co-occupy the same hydrate structure. Pair distribution functions (PDFs) provide atomic-scale structural insight into intermolecular interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…A promising method for sequestration is CO 2 storage in deep-oceanic sediments as gas hydrates. Gas hydrates are crystalline compounds made up of water and one or more hydrate-forming compound, such as CO 2 , methane, and other hydrocarbons. The hydrate-forming molecules are maintained in a metastable crystal lattice formed of water molecules by van der Waals forces within the hydrates , and offer high storage capacity (ideally 184 volumes of gas/volume of water) . Under sufficient depth from the surface, CO 2 hydrates could be formed on the seafloor or within the sediments. , Natural gas hydrates are stable and naturally found in oceanic sediments and permafrost locations, with traces of other gases, such as ethane, CO 2 , and H 2 S. Gas hydrates are stable in nature as a result of the prevalent high-pressure and low-temperature conditions in oceanic sediments and permafrost locations. CO 2 forms hydrate structure I (sI), and a unit cell is made up of 46 hydrogen-bonded water molecules with two dodecahedral cages and six tetrakaidekahedral cages, each of which may theoretically store one CO 2 molecule. , In a large mass of hydrates, some cages may be empty. Gas hydrates can act as a geological reservoir for CO 2 sequestration while also remaining stable as non-destructive structures, which might help to avoid problems, like seabed instability …”
Section: Introductionmentioning
confidence: 99%
“…A promising method for sequestration is CO 2 storage in deep-oceanic sediments as gas hydrates. Gas hydrates are crystalline compounds made up of water and one or more hydrate-forming compound, such as CO 2 , methane, and other hydrocarbons. The hydrate-forming molecules are maintained in a metastable crystal lattice formed of water molecules by van der Waals forces within the hydrates , and offer high storage capacity (ideally 184 volumes of gas/volume of water) . Under sufficient depth from the surface, CO 2 hydrates could be formed on the seafloor or within the sediments. , Natural gas hydrates are stable and naturally found in oceanic sediments and permafrost locations, with traces of other gases, such as ethane, CO 2 , and H 2 S. Gas hydrates are stable in nature as a result of the prevalent high-pressure and low-temperature conditions in oceanic sediments and permafrost locations. CO 2 forms hydrate structure I (sI), and a unit cell is made up of 46 hydrogen-bonded water molecules with two dodecahedral cages and six tetrakaidekahedral cages, each of which may theoretically store one CO 2 molecule. , In a large mass of hydrates, some cages may be empty. Gas hydrates can act as a geological reservoir for CO 2 sequestration while also remaining stable as non-destructive structures, which might help to avoid problems, like seabed instability …”
Section: Introductionmentioning
confidence: 99%
“…Next, we turn on the orientation of the CO 2 inside the sI clathrate cages. The average crystal CO 2 @sI structure has been characterized by diffraction and spectroscopy experiments, as well as computer simulations 18,28,46,48,55–57,101–105 . In particular, guest CO 2 molecules disorder has been determined by analyzing powder X‐ray diffraction data by means of direct‐space technique followed by Rietveld refinement, 48 the experimental 13C NMR lineshapes have been simulated by MD calculations, 55 and temperature dependent polar angle distributions for the CO 2 @T sI cages have been reported at T = 77 and 274 K, while more recently experimental neutron pair distribution functions of CO 2 hydrates at low temperature of 10 K have been analyzed by complementing MD simulations and reverse Monte Carlo fitting 105 .…”
Section: Resultsmentioning
confidence: 99%
“…18,28,46,48,[55][56][57][101][102][103][104][105] In particular, guest CO 2 molecules disorder has been determined by analyzing powder X-ray diffraction data by means of direct-space technique followed by Rietveld refinement, 48 the experimental 13 C NMR lineshapes have been simulated by MD calculations, 55 and temperature dependent polar angle distributions for the CO 2 @T sI cages have been reported at T = 77 and 274 K, while more recently experimental neutron pair distribution functions of CO 2 hydrates at low temperature of 10 K have been analyzed by complementing MD simulations and reverse Monte Carlo fitting. 105 Although earlier neutron diffraction studies and 13 C solidstate NMR experiments have concluded that the CO 2 molecules remain dynamically disorder in the CO 2 @sI hydrate cages, depending on the shape and size of the cavities average crystal structures with preferred CO 2 orientations have been reported within the cages. In particular, according to the neutron diffraction experiments, 13 C NMR and MD simulations 46,48,55,57,105 the nonspherical oblate shape of the sI large cages leads to preferential alignment of linear CO 2 molecules in directions parallel to the two hexagonal faces of the T cage.…”
Section: Quantum 5d Calculations Of the T-r Statesmentioning
confidence: 99%
“…When atomic models are available, techniques such as Reverse Monte Carlo (RMC) can be used to create precise matches between simulation and experiment. [24] With a strictly atomic model, RMC could preferentially adjust coordinates of atoms at the edges of crystallites to capture changes in the RDF due to configurational disorder. In HDRDF, we can imagine an analogous procedure in which RMC adjusts the coordinates of the atomic models for each phase, while leaving the mesoscale contribution intact.…”
Section: Hdrdf 3 Limitationsmentioning
confidence: 99%